Linguistic Purism in Bengali Language in Bangladesh: Myth and Reality - Abdul Awal (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2022)
The paper traces the historical development of "linguistic purism" worldwide as well as in Bangladesh. It also denotes the origin and development of the Bengali language in terms of pidginization and creolization. Furthermore, initiatives of linguistic purism in Bangladesh by linguistic purists and the government are explored from historical and socio-linguistic points of view. The myth and reality of linguistic purism in Bangladesh are explored with due reference. The issues (language pollution, language deteoration, language oppression, language extinction, language health, etc.) which are raised by language purists in Bangladesh are critically analyzed in this paper. The debate over "loan words" and "borrowing words," code-mixing, and code-switching is explained in the context of Bangladesh. The paper investigates the pros and cons of linguistic purism and its consequences for linguistic development in Bangladesh. How linguistic purism is related to linguistic human rights is vividly illustrated herewith.